Determination of the Normal Position of the Anus in Taiwanese Infants - Wai-Tao Chan; Hung-Chang Lee; Wei-Na Wang; Chun-Yan Yeung; Cheun-Bin Jiang (Elsevier, 2009)
Anterior displacement of the anus has been reported to be a cause of chronic constipation amongst young children. However, the normal position of the anus has not been studied in Taiwan. Patients and Methods: Normal anal positioning was studied in 200 neonates (100 males and 100 females). All of these individuals were non-constipated. The position of the anus was numerically defined by the anal position index (API), which is the distance from the center of the anus to the vagina or scrotum divided by the distance between the vagina or scrotum and the coccyx. Thirty non-constipated infants aged between 5 and 19 months (15 males and 15 females) were included in the study to compare the index between neonates and older infants. Results: The API values were 0.54±0.03 (95% CI, 0.48-0.60) for newborn males and 0.40±0.04 (95% CI, 0.32-0.47) for newborn females, 0.53±0.02 (95% CI, 0.49-0.57) for young boys and 0.39±0.06 (95% CI, 0.28-0.51) for young girls. The difference in indices between males and females was significant, but there was no significant difference in the indices between newborns and older infants. Conclusions: The API is independent of age, and provides a constant and reliable parameter for determining the position of the anus.